IMPROVING THE METHODOLOGY FOR DEVELOPING INDEPENDENT LEARNING AND EDUCATIONAL ASSIGNMENTS IN FUTURE PRIMARY SCHOOL TEACHERS (based on the subject of Children's Literature) - G.K.Raximova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article discusses the issue of improving the methodology of independent education and development of educational tasks for future elementary school teachers based on the subject of children's literature.